SOCIALITY AND MONETIZATION ON LIVE STREAMING PLATFORMS - Bowman, Nick; Johnson, Mark Richard; Woodcock, Jamie; Partin, Will; Jackson, Nathan (AoIR Selected Papers of Internet Research, 2020)
This panel presents ongoing research into online “live streaming” platforms, which offer the live broadcast of individuals’ activities - primarily but not exclusively digital gameplay - over the internet to potentially massive worldwide audiences. The largest platform in this area (on which we focus) is Twitch.tv, already the 30th most-viewed website in the world, with comparable platforms boasting large viewing numbers in China, Korea, and Japan. Our first talk examines Twitch as the dominant leading live streaming platform, outlining its evolution and historical origins while unpacking some of the fundamental user-platform relationships manifested on the site. The second addresses itself to the sociality of live streaming, which unlike traditional video media formats enables a rapid live exchange of comments and conversation between live streaming producers and consumers. The third paper presents an overview and typology of monetization methods in live streaming, focusing in particular on the gamified and “gamblified” elements of making money through the practice, as well as how these practices have evolved through a three-way dialogue between viewers, “streamers”, and platforms. The fourth paper builds on this by examining the on-platform currency of Twitch, known as “Bits”, and how the platform captured donations from viewers through the implementation of this currency system. The fifth and final paper will then further develop these critical enquiries into monetization methods and platform dynamics by presenting a number of extremely contemporary developments in this area on Twitch, exploring new the routes for capital flow enabled by new platform infrastructures and technological systems.